Ethnic sensitivity analyses of pharmacokinetics, efficacy and safety in polycythemia vera treatment with ropeginterferon alfa-2b - Qin, Albert; Wu, Daoxiang; Liao, Jason; Xie, Shuping; Chen, Haoqi; Gao, Yucheng; Cui, Jie; Su, Xia; Miyachi, Narihisa; Sato, Toshiaki; Li, Yaning; Zhang, Jingjing; et al. (Frontiers in Pharmacology, 2024)
Ropeginterferon alfa-2b (Ropeg) is approved for the treatment of adults with polycythemia vera (PV). This report aims to analyze the ethnic sensitivity of Ropeg for the treatment of PV, comparing the pharmacokinetics (PK), efficacy, and safety profiles across diverse ethnic groups. We conducted a relevant review of PV and analysis of data obtained from clinical studies involving Ropeg. The PK behavior of ropeg showed no significant differences between Chinese and overseas populations. Their efficacy and safety profiles were similar across the ethnic groups studied. The analyses indicated that the dose-exposure-response profile of Ropeg was consistent irrespective of ethnic variations. The results suggest that Ropeg exhibits a consistent PK and pharmacodynamics profile and a similar therapeutic effect across different ethnic groups, confirming its efficacy and safety in the global treatment of PV. More generally, these findings support the broader application of Ropeg in diverse patient populations and emphasize the need for an inclusive clinical practice.